2008
DOI: 10.1097/ftd.0b013e318185813d
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Highly Sensitive Liquid Chromatography/Mass Spectrometry Method for Simultaneous Quantification of Lenalidomide and Flavopiridol in Human Plasma

Abstract: Lenalidomide, an immunomodulatory agent, and flavopiridol, a broad cyclin-dependent kinase inhibitor, are both active therapies for clinical use in genomic high risk chronic lymphocytic leukemia (CLL). A high-performance liquid chromatographic assay with tandem mass spectrometric detection has been developed to simultaneously quantify lenalidomide and flavopiridol in human and mouse plasma to facilitate their combined clinical development. Samples were prepared by liquid-liquid extraction with acetonitrile- (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The lenalidomide was extracted from these tablets using the procedures outlined in "Methods" and confirmed to have very high purity by NMR and liquid chromatography/mass spectrometry analysis performed by The Ohio State University Pharmacoanalytical Shared Resource using a highly sensitive assay. 22 The NMR spectra contained only lenalidomide resonance peaks and had no indication of contaminating materials. This same assay is used to measure lenalidomide plasma concentrations as part of ongoing clinical trials at The Ohio State University.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lenalidomide was extracted from these tablets using the procedures outlined in "Methods" and confirmed to have very high purity by NMR and liquid chromatography/mass spectrometry analysis performed by The Ohio State University Pharmacoanalytical Shared Resource using a highly sensitive assay. 22 The NMR spectra contained only lenalidomide resonance peaks and had no indication of contaminating materials. This same assay is used to measure lenalidomide plasma concentrations as part of ongoing clinical trials at The Ohio State University.…”
Section: Discussionmentioning
confidence: 99%
“…The purity of capsule-extracted lenalidomide was evaluated with nuclear magnetic resonance (NMR) and liquid chromatography/mass spectrometry in The Ohio State University Pharmacoanalytical Shared Resource as published. 22 The NMR spectra contained only lenalidomide resonance peaks and had no indication of contaminating materials. Powdered lenalidomide was then resuspended in phosphate-buffered saline (PBS), pH 1.4 (vehicle).…”
Section: Lenalidomide Extraction and Purificationmentioning
confidence: 99%
“…The stock solutions and working standard of LND and IS were also stable for 15 days at refrigerator temperature (below 10°C) and for 12 h at room temperature. Therefore, LND was deemed to be stable upto 30 days at −80°C in spiked plasma and up to 15 days in aqueous solution in refrigerator, as reported previously [19]. …”
Section: Resultsmentioning
confidence: 80%
“…The first one employed liquid chromatography-mass spectrometry using single ion monitoring with a limit of quantitation of 5 ng/mL[18]. The second method included the simultaneous determination of LND and flavopiridol by liquid chromatography-mass spectrometry (LCMS/MS) using a single reaction monitoring (SRM) and a gradient elution [19]. Both methods have the disadvantages of long run time of 8 and 10 min respectively which does not meet the requirement of high throughput and speedy analysis of biosamples in clinical laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…C18 analytical columns can be used for both these drugs. Although the structures of these drugs are similar, it has been shown that APCI negative ionisation provides the most sensitivity for thalidomide analysis [198], whereas APCI positive ionisation is preferred for lenalidomide [199].…”
Section: Anticancer Drugsmentioning
confidence: 99%